A New Self-Defence Framework for Domestic Abuse Survivors Who Use Violent Resistance in Response - Bettinson, Vanessa; Wake, Nicola (The Modern Law Review, 2024)
This article criticises the government's rejection of proposals by the Prison Reform Trust that would have extended self-defence in householder cases to victims/survivors of domestic abuse. The authors argue that the Prison Reform Trust proposals should be enacted, and further supported by novel complementary reform of the option to retreat, and the exclusion of intoxicated mistaken belief in self-defence claims. Specifically, the authors advance a statutory rebuttable presumption regarding the option to retreat in cases involving domestic abuse, namely, an assumption that the victim/survivor was not realistically able to retreat safely, unless it is proven otherwise. The authors also examine the appropriateness of the policy decision to exclude intoxicated mistaken belief in all self-defence cases and advocate for its removal. It should be replaced with a requirement that all mistaken beliefs must be reasonable regardless of the presence of intoxication. Procedural recommendations are also advanced, including amendment of the Crown Court Compendium to include judicial directions on self-defence which adopt a social entrapment approach in domestic abuse cases, and supported by the admissibility of non-medical expert evidence on the nature and impact of coercive control.